Adverse selection, brokerage coverage, and trading activity on the Tokyo Stock Exchange - Ahn, Hee-Joon; Cai, Jun; Hamao, Yasushi; Ho, Richard Y.K. (Journal of Banking & Finance, 2005)
Limit-order trading mechanisms, corporate ownership structure, and incentive structures in the Japanese brokerage industry differ from those in the US in several important ways. This paper exploits these differences to examine the joint and cross-sectional determinants of adverse selection costs, brokerage coverage, and trading activity for a large sample of Japanese firms traded on the Tokyo Stock Exchange. We find that adverse selection costs are associated with firm characteristics but not with ownership characteristics, which implies that adverse selection costs are affected by inside trading rather than inside holdings. We also find that while brokerage coverage reduces adverse selection costs, higher adverse selection costs lead more brokerage firms to enter the market because of the greater profit potential. Finally, we find that causality also runs both ways between brokerage coverage and trading volume: brokerage coverage increases trading volume and trading volume increases brokerage coverage.